Dissipative Dynamic Covalent Chemistry (DDCvC) Based on the Transimination Reaction. Issue 26 (25th March 2022) - Del Giudice, Daniele; Valentini, Matteo; Melchiorre, Gabriele; Spatola, Emanuele; Di Stefano, Stefano
Abstract: This work reports that the composition of a dynamic library (DL) of interconverting imines can be controlled over time in a dissipative fashion by the addition of an activated carboxylic acid used as a chemical fuel. When the fuel is added to the DL, which is initially under thermodynamic equilibrium, the composition of the mixture dramatically changes and a new, dissipative (out of equilibrium) state is reached that persists until fuel exhaustion. Thus, a transient dissipative dynamic library (DDL) is generated that, eventually, reverts back to the initial DL when the fuel is consumed, closing a DL→DDL→DL cycle. The larger the amount of added fuel, the longer the time spent by the system in the DDL state. The transimination reaction is shown to be an optimal candidate for the realization of a dissipative dynamic covalent chemistry (DDCvC). Abstract : Dissipative dynamic libraries (DDLs) of imines are generated by addition of 2‐cyano‐2‐(4'‐chloro)phenylpropanoic acid employed as a chemical fuel to equilibrated dynamic libraries (DLs). At the addition of the fuel the initial composition of the library dictated by the thermodynamic equilibrium is perturbed and a transient, temporal controllable, out of equilibrium state is obtained, which reverts to the initial equilibrium when the fuel is exhausted.